Unravelling the Scientific Debate on How to Address Wolf-Dog Hybridization in Europe - Donfrancesco, Valerio; Ciucci, Paolo; Salvatori, Valeria; Benson, David; Andersen, Liselotte Wesley; Bassi, Elena; Blanco, Juan Carlos; Boitani, Luigi; Caniglia, Romolo; Canu, Antonio; Capitani, Claudia; Chapron, Guillaume; et al. (Frontiers in Ecology and Evolution, 2019)
Anthropogenic hybridisation is widely perceived as a threat to the conservation of biodiversity. Nevertheless, to date, relevant policy and management interventions are unresolved and highly convoluted. While this is due to the inherent complexity of the issue, we hereby hypothesise that lack of agreement concerning management goals and approaches, within the scientific community, may explain the lack of social awareness on this phenomenon, and the absence of effective pressure on decision-makers. By focusing on wolf x dog hybridisation in Europe, we hereby (a) assess the state of the art of issues on wolf x dog hybridisation within the scientific community, (b) assess the conceptual bases for different viewpoints, and (c) provide a conceptual framework aiming at reducing the disagreement. We adopted the Delphi technique, involving a three-round iterative survey addressed to a selected sample of experts who published on Web of Science listed journals, in the last ten years on wolf x dog hybridisation and related topics. Consensus was reached that admixed individuals should always be defined according to their genetic profile, and that a reference threshold for admixture (i.e., q-value in assignment tests) should be formally adopted for their identification. To mitigate hybridisation, experts agreed on adopting preventive, proactive and, when concerning small and recovering wolf populations, reactive interventions. Overall, experts’ consensus seemed to wane as the issues addressed became increasingly pragmatic, including the adoption of lethal removal. We suggest three non-mutually exclusive explanations for this trend: (i) value-laden viewpoints increasingly emerge when addressing pragmatic issues, and are particularly diverging between experts of different educational background (e.g., ecologists, geneticists); (ii) some experts prefer avoiding the risk of giving carte blanche to wolf antagonists to (illegally) remove wolves, based on the wolf x dog hybridisation issue; (iii) room for subjective interpretation and opinions results from the paucity of data on the effectiveness of the different management interventions. These results have management implications and reveal gaps of knowledge on a wide spectrum of issues related not only to the management of anthropogenic hybridisation, but also to the role of ethical values and real-world management concerns in the scientific debate.